Evaluasi terhadap Program Mikrotrans Terintegrasi dalam Pengelolaan Sistem Transportasi Umum di Jakarta Timur: Indonesia - Lubis, Petrik Manuel; Cadith, Juliannes (Epistemik Press, 2025)
The aim of this study was to assess the implementation of the Mikrotrans program and evaluate whether it has effectively provided comfort and security to the public, aligning with the program’s intended goals. A descriptive qualitative approach was employed, utilizing observations, interviews, and documentation. The study used the CIPP evaluation model, which includes evaluations of context, input, process, and product. The findings show that the context evaluation aligns with community needs and the program’s goals. Input evaluation reveals that the planning, budget, and resources are adequate to meet the targets. However, the process evaluation indicates that the implementation of the Mikrotrans program is still incomplete. While the product evaluation reflects positive outcomes, the overall execution has not yet reached optimal effectiveness, highlighting the need for further improvements and sustainable development of the program.